IT resources and business survival: competitive advantage revisited - Piñeiro Sánchez Carlos (Estudios de Economía, 2020)
The study of firms’financial imbalances has been a common topic in research over the last decades; however, some aspects of the failure processes have received little attention. This research deepens into the temporal dimension of bankruptcy, and explores whether IT resources affect the expected lifetime of a firm. Drawing on the resource-based view of the firm, we design and adjust a Cox regression. We found evidence that the average lifetime and the odds of surviving beyond any arbitrary time t are modified by the availability and the pattern of use of marketing-oriented IT resources, by IT management experience, and by the ability to deploy internal and external collaboration strategies. The results are robust when considering the industry and the financial situation of each company.